Clinical Significance of Venous Anomalies in Syndromic Craniosynostosis. Issue 1 (January 2018) - Copeland, Andrea E.; Hoffman, Caitlin E.; Tsitouras, Vassilios; Jeevan, Dhruve S.; Ho, Emily S.; Drake, James M.; Forrest, Christopher R.
Abstract : Background: The pattern of cranial venous drainage in syndromic craniosynostosis is unpredictable and not adequately understood. Collateral channels substitute for stenotic venous sinuses and pose potential risk for surgical intervention. The purpose of this study was to analyze the patterns of venous drainage in patients with syndromic craniosynostosis and their influence on operative planning and morbidity. Methods: A retrospective study of patients with syndromic craniosynostosis from 2000 to 2013 was performed. Demographic data were collected including phenotype and associated pathologies. Pre- and/or postoperative venous imaging was reviewed for venous sinus stenosis, collateral emissaries, and persistent fetal sinuses. Categorization of anomalous venous drainage was performed, and the relationship with surgical morbidity was assessed. Results: Forty-one patients were identified. Anomalies were present in 31 patients (76%) consisting of dural sinus stenosis in 28 (68%), dilated emissaries in 26 (63%), and fetal sinuses in 7 (17%). Pfeiffer syndrome was most commonly associated with anomalous drainage (100%). Venous anomalies were associated with elevated intracranial pressure (ICP), shunted hydrocephalus, Chiari malformations, and sleep apnea. In 5 cases, the surgical plan was adjusted based on anomalous anatomy. No mortalities occurred. Intraoperative complication rate was 7.3%, all with anomalous drainage. Median estimated blood loss was 1, 100 cc for patients with anomalies versus 400 cc without anomalies ( P = 0.181). Conclusion: Cranial venous anomalies are commonly detected in patients with syndromic craniosynostosis and may affect surgical morbidity and outcome with a higher estimated blood loss, alteration of procedure, and postoperative morbidity. Detailed preoperative imaging of the venous drainage is therefore recommended in cases of syndromic synostosis.